What is the underlying structure of the climate, conflict, and socio-economic system in Kenya? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Kenya, using network analysis. The climate, conflict nexus in Kenya is strongly dependant on the ability of the agricultural sector to adapt to climate shocks which is mediated by two underlying pillars, 1) the level of education of a household, and 2) the nutritional security of those households